Characterization of Gibberellin Producing Rhizobacteria Isolated from Soil Forest in Banten - Hadi Susilo; Nisa Rachmania Mubarik; Triadiati Triadiati (Current Biochemistry, 2015)
Gibberellin is plant growth regulator that stimulates cell elongation, seed germination, flowering, and fruit ripening. This study was conducted to isolate, identify, and optimize growth media for gibberellins producing- rhizobacteria isolated from rhizosphere soil of “keruing“ (Dipterocarpus sp.) tree in forest research Carita, Pandeglang, Banten. Eight bacterial isolates were obtained and all produced gibberellin. The BC2 isolate produced the highest of gibberellin (0.897 mg mL-1) and then selected for identification based on physiology, molecular character, and effects of growth media with variation of temperature, pH, and light. The result of physiological test indicated that BC2 isolate does not produce indole, positive on urease and oxidative carbohydrate. The phylogenetic analysis showed that BC2 isolate is belonged to Stenotrophomonas maltophilia with 98% similarity level. The optimation of growth media indicated that the growth of BC2 isolate was optimum at 30°C, pH 7, and dark condition.